Seismic capacity of buttressed masonry arches. (15th July 2020) - Brandonisio, Giuseppe; Angelillo, Maurizio; De Luca, Antonello
Highlights: The seismic capacity of masonry buttressed arches with a circular shape is examined. The influence of geometry on arch seismic capacity is investigated by using L.A. The results are discussed in terms of failure mechanism and lateral strength. Abstract: Masonry buttressed arches have been designed in the past for vertical actions deriving from gravity loads and horizontal actions determined by the thrust of the arch. Horizontal actions consequent to earthquake motions were not usually taken into account in the design of these structures. This, despite of the high vulnerability of such typology, frequently characterizing monumental buildings. This paper addresses the problem of the capacity of buttressed masonry arches with a circular shape and different angles of embrace, under horizontal actions induced by seismic motions. To this aim, in the framework of Limit Analysis for masonry structures, the seismic analysis of a large sample of buttressed arches is provided and discussed. The outcomes of numerical analysis have shown that the activated failure mechanisms change in presence of horizontal actions. The results of the analysed large sample are very consistent in terms of lateral capacity since the horizontal load multiplier increases with the thickness of the buttresses and decreases with the buttress slenderness. The paper provides an unexpected result for thin arches since in this case semi-circular arches become more vulnerable than segmental.